Immunologicheskie aspekty sportibnoi deyatel'nosti cheloveka - Suzdalnitskij, R. S.; Levando, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The purpose of this paper was to reveal the general tendency of a man`s immunity system`s adaptation to physical loads. The stated dynamics of changes in an athlete`s immunity status allowed to identify at least four phases of adaptation: - phase of mobilization; - phase of compensation; - phase of decompensation; - phase of restitution The authors consider the general problems of sports immunology, the methods of prophylaxis and compensation of the sports stressor immunodeficit states.